Transesophageal echocardiography in perioperative period guiding the decision making during hemodynamic instability due to atrial fibrillation - Pontes,João Paulo Jordão (2019)
Abstract Background and objective: Atrial fibrillation is the most common cardiac arrhythmia, which may occur during the perioperative period and lead to hemodynamic instability due to loss of atrial systolic function. During atrial fibrillation management, electrical cardioversion is one of the therapeutic options in the presence of hemodynamic instability; however, it exposes the patient to thromboembolic event risks. Transesophageal echocardiography is a diagnostic tool for thrombi in the left atrium and left atrial appendage with high sensitivity and specificity, allowing early and safe cardioversion. The present case describes the use of transesophageal echocardiography to exclude the presence of thrombi in the left atrium and left atrial appendage in a patient undergoing non-cardiac surgery with atrial fibrillation of unknown duration and hemodynamic instability. Case report: Male patient, 74 years old, hypertensive, with scheduled abdominal surgery, who upon cardiac monitoring in the operating room showed atrial fibrillation undiagnosed in preoperative electrocardiogram, but hemodynamic stable. During surgery, the patient showed hemodynamic instability requiring norepinephrine at increasing doses, with no response to heart rate control. After the end of the surgery, transesophageal echocardiography was performed with a thorough evaluation of the left atrium and left atrial appendage and pulsed Doppler analysis of the left atrial appendage with mean velocity of 45 cm.s-1. Thrombus in the left atrium and left atrial appendage and other cardiac causes for hemodynamic instability were excluded. Therefore, electrical cardioversion was performed safely. After returning to sinus rhythm, the patient showed improvement in blood pressure levels, with noradrenaline discontinuation, extubation in the operating room, and admission to the intensive care unit. Conclusion: In addition to a tool for non-invasive hemodynamic monitoring, perioperative transesophageal echocardiography may be valuable in clinical decision making. In this report, transesophageal echocardiography allowed the performance of early and safely cardioversion, with reversal of hemodynamic instability, and without thromboembolic sequelae.